A Festa do Divino em Viana no século XXI: memórias afetivas na construção de uma açorianidade capixaba - Mariano, Fabiene Passamani (2019)
The beginning of the nineteenth century was a period of intense political, economic and sociocultural changes for the Captaincy of Espírito Santo, resulting from a new development mentality of the Colony, which emerged after the arrival of the Portuguese Royal family in Brazil. With this new perspective, the Espírito Santo emerged on the national scene and, in 1813, was founded the Agricultural Colony of Viana with the settlement of native Portuguese immigrants from the Azores Islands. The Azorean families, in addition to seeking economic and social success, also brought their cultural background in which clearly stands out the object of study of this thesis: the Feast of the Divine Holy Spirit. The Feast of the Divine, as it is called, has been taking place in Viana since 1817 - the same year as the inauguration of the parish of Nossa Senhora da Conceição. It is a bicentennial festival, full of material and immaterial symbolism, which preserves its structure the ritual script similar to the one which still occurs in the Azores, however, maintaining some characteristics of the local culture. In this study, we revisit the historical context of the arrival of the Azoreans, as well as their settlement in the Captaincy of Espírito Santo; the emergence of the Feast in Portugal; the way the festival is held in the Azores; the diffusion of the Feast in North American countries and Brazil and, finally, the Feast in Viana itself, analyzed basing on written documents, photographs, narratives and participant observation during the preparation and realization of the Feast accompanied by the author in the 21st century.